(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article defines role of intercultural communication in society and analyses reasons why intercultural communication is important This works also includes information about the term culture. Intercultural communication is correspondence between individuals with contrasting social personalities. Culture and character are made, comprehended, and changed through intercultural correspondence. Business is almost borderless, so it’s important to learn how to communicate effectively and respectfully with people from other cultures. Studying intercultural communication can also help you become more self-aware.